2023
DOI: 10.1042/bst20220584
|View full text |Cite
|
Sign up to set email alerts
|

The central role of translation elongation in response to stress

Abstract: Protein synthesis is essential to support homeostasis, and thus, must be highly regulated during cellular response to harmful environments. All stages of translation are susceptible to regulation under stress, however, the mechanisms involved in translation regulation beyond initiation have only begun to be elucidated. Methodological advances enabled critical discoveries on the control of translation elongation, highlighting its important role in translation repression and the synthesis of stress-response prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Although many studies concluded that the translation initiation dominantly determines the protein synthesis rate in growing cells 59,7582,84 . On the other hand, under stressed conditions, the perturbed elongation rate determines the protein production rate 8587 . Importantly, our method provides a useful tool to understand kinetic relationships between translation initiation and elongation in wide arrays of cellular situations.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies concluded that the translation initiation dominantly determines the protein synthesis rate in growing cells 59,7582,84 . On the other hand, under stressed conditions, the perturbed elongation rate determines the protein production rate 8587 . Importantly, our method provides a useful tool to understand kinetic relationships between translation initiation and elongation in wide arrays of cellular situations.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that codons can influence translation implies that the elongation step must be affected. Oxidative stress can slow down translation elongation through various means 37 . However, in this study, initiation is still the rate-limiting step because the translation bias we detected from sequencing was reproduced in the luciferase reporter assays, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While genomic and transcriptomic induction of stress-specific gene expression programs have been extensively investigated (Mascarenhas et al, 2008;Taymaz-Nikerel et al, 2016), many aspects of the induction at the proteomic level remain unclear. In response to many forms of stress, cells suppress global translation while simultaneously inducing the production of selective stress-response proteins (Barros et al, 2023;Shenton et al, 2006). This global suppression is crucial to prevent damage to newly synthesized proteins, prevent toxic gain-of-functions, and minimize extraneous energy expenditure on non-essential proteins (Holcik & Sonenberg, 2005).…”
Section: Introductionmentioning
confidence: 99%